2020
DOI: 10.3390/s20174996
|View full text |Cite
|
Sign up to set email alerts
|

Fast Wearable Sensor–Based Foot–Ground Contact Phase Classification Using a Convolutional Neural Network with Sliding-Window Label Overlapping

Abstract: Classification of foot–ground contact phases, as well as the swing phase is essential in biomechanics domains where lower-limb motion analysis is required; this analysis is used for lower-limb rehabilitation, walking gait analysis and improvement, and exoskeleton motion capture. In this study, sliding-window label overlapping of time-series wearable motion data in training dataset acquisition is proposed to accurately detect foot–ground contact phases, which are composed of 3 sub-phases as well as the swing ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…In 2020 another approach using a CNN was presented by Jeon et al [ 16 ] reaching 99.8% accuracy, but having a huge drop in accuracy when testing with unseen data. In this paper, a new ConvLSTM approach is presented to automatically divide the time series into its gait phases, with higher granularity and individuality compared to other papers before.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020 another approach using a CNN was presented by Jeon et al [ 16 ] reaching 99.8% accuracy, but having a huge drop in accuracy when testing with unseen data. In this paper, a new ConvLSTM approach is presented to automatically divide the time series into its gait phases, with higher granularity and individuality compared to other papers before.…”
Section: Introductionmentioning
confidence: 99%
“…In their works, ref. [17] used windowed data as well to perform training on a two-dimensional format matrix. Related works such as [18,19] showed that the window size can be chosen based on a compromise between the accuracy and the training time, and for smaller values of the window size, we get a higher accuracy.…”
Section: Data Preparationmentioning
confidence: 99%
“…Models such as Naive Bayes were also used in the context of the study [30]. Hence, deep neural architectures can be used whether for the same configuration or for pre-processed and raw signals, especially CNN models that are commonly used and have shown their efficiency on raw data through the works of [17]. Furthermore, CNN architectures can also be used on sequential inputs by applying one-dimensional convolutional layers to each component of the different signals; ref.…”
Section: Neural Architecturesmentioning
confidence: 99%
“…Since the lower limb exoskeleton is powered by motor-driven joints, including the hip and knee f/e, the planned Cartesian position coordinates of the ankle and hip joints should be converted to the joint space through inverse kinematics as shown in Equations ( 10)- (14). Consecutive steps of walking are simulated with a sequence of stride lengths, L stride = [1245, 1150, 1050, 950, 850, 750, 650].…”
Section: Gait Planning Algorithm Simulationmentioning
confidence: 99%
“…Therefore, gait planning online or offline with additional measured information has been studied in recent years. Jeon et al presented a fast wearable sensor-based gait phase classification method with the help of a convolutional neural network, which represents human-machine walking intention and is useful for exoskeleton motion control [ 14 ]. The polymer optical fiber sensors reported by Leal-Junior et al show promising application scenarios for soft and wearable gait measurement for exoskeleton online gait planning [ 15 ].…”
Section: Introductionmentioning
confidence: 99%